Konsep Pendidikan Agama Islam Menurut Pandangan KH. M.A Sahal Mahfudz - edy; Munzilah Ramdani (Edusifa: Jurnal Pendidikan Islam, 2024)
Historically, Muslims experienced the peak of progress because they were driven by the development of scientific work. Then when Muslims enter the abyss of decline, it is always accompanied by the decline of monumental works of scientific discoveries. This review suggests the need for efforts to preserve the intellectual treasures of earlier Muslims. That way, in order to know the historicity of their thinking. Academic anxiety led the author to al-Marhumm KH. M.A. Sahal Mahfudz. However, because his figure is less well known in the national education discourse. So it needs serious proof. Therefore, this study aims to reveal the concept of Islamic religious education in the view of KH. M.A. Sahal Mahfudz. Research is a product of qualitative research type library research. The author uses a historical-philosophical approach. Data collection is done by means of documentation, including the authors determining the primary and secondary data sources. The data were analyzed using a content analysis method, the ideas contained in the primary and secondary data were confronted critically. In this case the data is examined from general ideas, then drawn to specific ideas in order to produce objective conclusions. There is a problem formulation in this study, namely; How is the concept of Islamic education according to the view of KH. M.A. Sahal Mahfudz ? The results showed philosophically the concept of Islamic religious education in the view of KH. M.A. Sahal Mahfudz was motivated by his thoughts on the human personality with its various dimensions, both physical and spiritual, especially the human personality as khalifatullah who has the responsibility to educate and maintain the survival of the universe. According to him, Islamic religious education is a process of interaction from educators, students and parents, an environment that leads to the formation of the Islamic character of students. The goal is to prepare pious students. In this case, students are seen as objects and subjects of education. The function of educators is as a facilitator, dynamist and motivator. The educational curriculum must be integrative and able to build student awareness. So the concept is relevant for the development of PAI today, especially to prepare cadres of people who have deep religious knowledge, shalih, and nakram.   Keywords: KH. M.A. Sahal Mahfudz, Concept of Islamic Religious Education